2014
DOI: 10.1063/1.4896733
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial thermal resistance and thermal rectification between suspended and encased single layer graphene

Abstract: With molecular dynamics simulations, we systematically investigate interfacial thermal resistance between suspended and encased single layer graphene. Combining with lattice dynamics analysis, we demonstrate that induced by substrate coupling which serves as perturbation, the long wavelength flexural phonon mode in the encased graphene is significantly suppressed when compared with that in the suspended graphene. Therefore, at the interface between suspended and encased graphene, in-plane phonon modes can tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 51 publications
(60 reference statements)
6
50
0
Order By: Relevance
“…Thus with the increase of system length, the difference between the two overlapped phonon energies is reduced, and the thermal rectification becomes weak in this system. According to the overlapped phonon energy at different conditions, it is observed that the difference in the overlap of the phonon spectra is the origin of the thermal rectification phenomena and our results conform with the previous studies [16,17,21,22].…”
Section: Vdosðnþsupporting
confidence: 94%
See 3 more Smart Citations
“…Thus with the increase of system length, the difference between the two overlapped phonon energies is reduced, and the thermal rectification becomes weak in this system. According to the overlapped phonon energy at different conditions, it is observed that the difference in the overlap of the phonon spectra is the origin of the thermal rectification phenomena and our results conform with the previous studies [16,17,21,22].…”
Section: Vdosðnþsupporting
confidence: 94%
“…For both Si/ C ratios, the increase in jDj results in the increase in the rectification factor akin to the characteristic in electric rectifier. With jDj ¼ 0.5 and Si/C ratio of 5%, the thermal rectification of asymmetric graphene structure is 145%, which overwhelms the carbon nanotube based thermal rectifiers like carbon nanocone [21] and carbon nanotube intramolecular junctions [22] and is comparable to other graphene based thermal rectifiers [13,16,17]. Our result demonstrates that such asymmetric graphene structures have an obvious advantage when applied in nanoelectronic devices.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…To understand the difference of interfacial thermal conductance at ZZ and ZZ57 interfaces, the phonon transmission process across the interfaces was investigated using the phonon wave packet method 45,46 . Phonon wave packets are formed from a linear combination of vibration eigenstates of the crystalline lattices.…”
Section: In-plane Interfacial Binding Between Mos 2 and Graphenementioning
confidence: 99%